BBS10 encodes a vertebrate-specific chaperonin-like protein and is a major BBS locus - ELÇİOĞLU, HURİYE NURSEL (NATURE PUBLISHING GROUP, 2006)
Bardet-Biedl syndrome (BBS) is a genetically heterogeneous ciliopathy. Although nine BBS genes have been cloned, they explain only 40-50% of the total mutational load. Here we report a major new BBS locus, BBS10, that encodes a previously unknown, rapidly evolving vertebrate-specific chaperonin-like protein. We found BBS10 to be mutated in about 20% of an unselected cohort of families of various ethnic origins, including some families with mutations in other BBS genes, consistent with oligogenic inheritance. In zebrafish, mild suppression of bbs10 exacerbated the phenotypes of other bbs morphants.
Keywords: BARDET-BIEDL-SYNDROME; GENE; DISORDER; GENOMICS